O movimento ambiental e o #florestafazadiferença no facebook: um diálogo sobre ciberativismo na sociedade midiatizada - Azevedo, Ana Paula da Silva (2014)
Communication technologies that are part of everyday life are creating new ways to interact and even rearrange old society demands. Inside the collective actions context, specifically in environmental activism, mediated communication is presented as a source of considerable importance, but the consequences and ramifications are still little known. In this context, this research aims to analyze the appropriation of the Internet and New Technologies of Information and Communication (NTIC) thru environmental activism, based on the trajectory of the movement “Floresta Faz a Diferença” – FFD - on Facebook. We try to verify how cyberactivism is developed by the Environmental Movement - MA, whereas the FFD was conducted by the Committee in Defense of Brazil Forests and Sustainable Development which brought together nearly 200 civil society organizations to mobilize people against the adoption of the “Projeto de Lei Complementar” (PCL 30/2011) with proposed changes to the forest Code of the country. The north of our reflections relies on the concept of mediatization as the process by which society has transformed the basis of its organization, incorporating new media values to the individual and collective social practices. We look forward to understand how the making process of activist generated by NICT works, discussing the supposed loss of its Brazilian MA roots, as Alexander Agrippa (2000) argues. The research highlights the mobilizing potential of social media networks generated by media ecology that orchestrates the interaction and relationship of mutual influence which has established itself among the most new media (transmitter / individual) and traditional media (capitalist corporations). We identify a strong presence of the media capital in the cyber activists FFD practices in social media networks as we emphasize the status of cooperation in the proceedings on the cultural dynamics of appropriation of the internet as the ambience in which new practices thrive in a culture of constant training . The MA represented by FFD follows an activist role that excels in media coverage of their actions in favor of mobilization that strengthens, in the online world, building a multiple sensorial identity (VIOLA, 1992). Thus, reinforces the importance of distinguishing this strong mobilizer character of network communication, the power of political transformation on the complexity brand that involves communication in contemporary society and matters concerning some risks on emptying the content of environmentalist message caused by discursive adaptations among different sectors that compose it, especially with the media coverage of its activism.